PENERAPAN METODE TAHSIN DALAM MENINGKATKAN KOMPETENSI MEMBACA DAN MENGHAFAL AL-QUR’AN DI MTS SALAFIYAH KOTA BANDUNG - Komarudin, Komarudin; Wasilah, Gina (Prodi Pendidikan Agama Islam STAI Darul Falah, 2023)
This research is motivated by the large number of students who are not yet fluent in reading or memorizing the Al-Qur'an, especially in knowing how to read the Al-Qur'an properly and correctly. This research aims to increase students' competence in reading and memorizing the Al-Qur'an. The lesson that supports the achievement of this program is by applying the tahsin method, because applying the tahsin method can help and make it easier for students to learn the knowledge of the Koran. The tahsin method used is learning how to read the Al-Qur'an well and in accordance with what the Prophet Muhammad taught. This research uses qualitative descriptive research methods, it can be said that research prioritizes descriptive analysis of an event or process as it occurs in the environment or nature to gain a deeper understanding of the nature of the process. Using this method can make it easier for researchers to find something. findings include the tahsin method, the results of applying the tahsin method as well as supporting and inhibiting factors regarding the local content of tahsin. It can be concluded that 1) The application of the tahsin method is quite efficient in implementing learning. It is implemented using three stages, including the iqra stage, the ummi stage and the talaqqi stage, 2) The results of the application of the tahsin method can improve students' competency results in reading and memorizing the Al-Qur'an, 3) Supporting and inhibiting factors in implementing the tahsin method include factors from the teacher, factors from students and factors from parents.